Revised System for the Classification of Exchange Rate Arrangements - Kokenyne, Annamaria (IMF Working Papers; Working Paper, 2009)
Since 1998, the staff of the International Monetary Fund has published a classification of countries' de facto exchange rate arrangements. Experience in operating this classification system has highlighted a need for changes. The present paper provides information on revisions to the system in early 2009. The changes are expected to allow for greater consistency and objectivity of classifications across countries, expedite the classification process, conserve resources, and improve transparency.